Access database design & programming: Creating programmable database applications with Access 97, 2000, 2002 & 2003 - Roman, S. Steven Roman (Beijing: O'Reilly Media, 2002)
The book gives description of general principles of database design, then describes the "relational algebra" that defines the meaning of such operations as unions and joins, introduces SQL syntax, and finally dives into the details of using VBA (Visual Basic for Applications) to write Access code. The result is a single book that can teach you all the basics of building database applications in Access. Portions of the book are heavy with logical equations whose effects can be hard to visualize, but Roman's judicious use of sample data makes it much easier to follow the operations being described
Includes appendixes and index
Keywords: Database design and programming